Application Of Problem-Based Learning (PBL) - Apuannor Apuannor (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to identify the impact of implementing Problem-Based Learning (PBL) techniques on the learning outcomes in economics for vocational high school (SMK) students. This research is based on the low level of student engagement in economics learning, which is still dominated by conventional methods, which impacts learning outcomes. The method used is a quantitative approach with a pre-test and post-test design in two groups: an experimental class using PBL and a control class using conventional learning.The subjects of the study were 10th-grade students of the Economics and Business program at SMK Negeri 1 Kota Besi. Data were collected through learning achievement tests before and after treatment, then analyzed using the Independent Samples Test. The results of the analysis showed that the average student learning outcome in the PBL class was 81, while in the non-PBL class it was 82. The hypothesis test showed a significance value (Sig. 2-tailed) of 0.231, which is greater than 0.05, so it can be concluded that there is no significant difference in learning outcomes between the two groups. However, the application of the PBL model is able to increase student activity, cooperation, and critical thinking skills in the learning process.